Handbook of sports medicine and science : the female athlete - Mountjoy, Margo L.; International Olympic Committee (Hoboken, New Jersey : Wiley Blackwell, 2014)
This new International Olympic Committee (IOC) handbook covers the science, medicine and psycho-social aspects of females in sports at all levels of competition. Each chapter focuses on the specific issues that female athletes confront both on and off the field, such as bone health, nutritional recommendations, exercise/competition during menstruation and pregnancy, and much more. Fully endorsed by the IOC and drawing upon the experience of an international team of expert contributors, no other publication deals with the topic in such a concise and complete manner.
Training the female athlete / Suzanne Hecht and Liza Arendt -- Injury prevention in the female athlete / Carolyn A. Emery and Constance M. Lebrun -- Psychology of the female athlete / Joan L. Duda and Saul Marks -- Nutritional guidelines for female athletes / Louise M. Burke -- Disordered eating and eating disorders in female athletes / Monica Klungland Torstveit and Jorunn Sundgot-Borgen -- Bone health / Naama W. Constantini and Constance M. Lebrun -- Menstrual health in the female athlete / Madhusmita Misra -- Exercise and pelvic floor dysfunction in female elite athletes / Kari Fasting -- Female athlete triad / Marci Goolsby -- Hyperandrogenism and gender change / Martin Ritzin -- Sexual harassment and abuse in sport : implications for health care providers / Trisha Leahy and Kari Fasting -- Exercise and pregnancy / Alejandro Lucia, Jonatan Ruiz, and Ruben Barakat -- The paralympic female athlete / Cheri Blauwet.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Women athletes -- Health and hygiene; Women athletes -- Physiology; Women athletes -- Psychology; Sports medicine; Athletic Injuries; Women's Health; Athletes -- psychology; Sports Medicine -- methods; Women -- psychology; Athletes -- Psychology; Athletic injuries; Sports medicine -- Methods; Women -- Psychology; Women's health; MEDICAL -- Surgery -- General; Sports medicine; Women athletes -- Health and hygiene; Women athletes -- Physiology; Women athletes -- Psychology; Electronic books